Institutions of law in the metaverse - Joxerramon Bengoetxea; Roberto Leopoldo Cruz Balbuena (Oñati Socio-Legal Series)
This paper scrutinizes the metaverse's burgeoning impact on the digital landscape and legal systems, emphasizing the imperative for legal adaptation to match technological strides. We explore the widening gap between law and technology, redefining norms and institutions alongside evolving concepts of personhood and civil society. Central inquiries focus on metaverse regulation and its transformative societal implications, urging interdisciplinary collaboration to comprehend its complexities. We caution against inaction, stressing the urgent need for a new jurisdiction safeguarding personal data and property rights. We advocate for comprehensive governance frameworks akin to those addressing climate change, ensuring future generations confront neither the repercussions of our inactivity nor the challenges posed by this challenging technological frontier.